„Pan Tadeusz” po angielsku. Spory wokół wydania i przekładu - Budrewicz, Aleksandra (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2018)
This publication is devoted to numerous polemics and discussion that accompanied the English translation of Pan Tadeusz by Adam Mickiewicz (1885). The translator was Maude Ashurst Biggs (1857–1933), an English woman, fascinated in the literature and culture of Poland. The introduction discusses the life of Biggs, the role of Edmund S. Naganowski in the completion of the translation, attempts at the time by Michał Dziewicki to translate this work by Mickiewicz and the role of William Richard Morfill. The principal part of the study is an anthology of articles that arose on the occasion of the above-mentioned polemics. Reviews of the translation from the Polish press and that from abroad were also included. The texts from the press that were reprinted in this publication concern foremost all of the polemics around the publication of the discussion. Other texts discuss the controversy around the translation. Several fragments of the correspondence of M. Biggs that appeared in Kronika Rodzinna were included as well.
Praca powstała w ramach projektu badawczego NPRH nr 11H 16 0131 84.
Keywords: Pan Tadeusz; Maude Ashurst Biggs; polemika krytycznoliteracka